Welding method for quartz glass
By coating nano -silver slurry in the binding surface of the quartz glass and to be connected to the materials, and melting welding joints in vacuum welding equipment to form a welding joint, it solves the problem of easy cracking when the quartz glass connection is cracked, and high -intensity and reliability connections are achieved.
Patent Information
- Application Number
- CN202411571506.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-05
Smart Images

Figure CN119347026A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of material brazing, and in particular to a welding method for quartz glass. Background Art
[0002] Quartz glass is widely used in optics, electronics, aviation and other fields due to its excellent optical properties, high temperature resistance and chemical stability. However, due to its low thermal expansion coefficient and high hardness, quartz glass is prone to cracking when connected to other materials, resulting in reduced connection strength. Summary of the invention
[0003] In view of this, the embodiments of the present application hope to provide a welding method for quartz glass with high connection strength.
[0004] In order to achieve the above-mentioned purpose, the technical solution of the embodiment of the present application is implemented as follows:
[0005] The embodiment of the present application discloses a welding method for quartz glass, comprising:
[0006] preparing nano silver slurry;
[0007] Coating the nano silver paste on the bonding surface of the quartz glass and the material to be connected;
[0008] Bringing the bonding surface of the quartz glass into contact with the bonding surface of the material to be connected, and melting the nanosilver paste to form a welding joint;
[0009] The weld joint, the quartz glass and the materials to be joined are cooled.
[0010] In one embodiment, the preparation of the nano silver paste comprises:
[0011] The nano silver particles are dispersed in an organic solvent, and a binder and a dispersant are added, and then stirred evenly to form the nano silver slurry.
[0012] In one embodiment, the organic solvent is ethanol and / or isopropanol; and / or,
[0013] The adhesive is polyvinyl alcohol or polyethylene glycol.
[0014] In one embodiment, the particle size of the nanosilver particles is between 10 nm and 100 nm; and / or,
[0015] The weight percentage of the nano-silver particles in the nano-silver paste is 10% to 50%.
[0016] In one embodiment, the thickness of the nano-silver paste on the bonding surface is between 40 μm and 50 μm.
[0017] In one embodiment, before the nanosilver paste is coated on the bonding surface of the quartz glass and the material to be connected, the welding method includes:
[0018] The quartz glass and the material to be connected are sequentially cleaned with an organic solvent, cleaned with an ultrasonic wave and cleaned with a plasma.
[0019] In one embodiment, during the melting of the nano-silver paste, a set pressure is applied between the quartz glass and the material to be connected.
[0020] In one embodiment, the set pressure is between 1 MPa and 5 MPa.
[0021] In one embodiment, a vacuum brazing device is used to melt the nano silver paste at a set temperature, and the vacuum degree in the vacuum brazing device is 1×10 -3 Pa to 1×10 -5 Pa, and the set temperature is between 200°C and 350°C.
[0022] In one embodiment, the cooling rates of the weld joint, the quartz glass and the material to be connected are between 1° C. / min and 10° C. / min.
[0023] The embodiment of the present application discloses a welding method for quartz glass, which comprises first preparing a nanosilver slurry, then coating the nanosilver slurry on the bonding surface of the quartz glass and the material to be connected, then contacting and abutting the bonding surface of the quartz glass with the bonding surface of the material to be connected, then melting the nanosilver slurry to form a welding joint, and finally cooling the welding joint, the quartz glass and the material to be connected. On the one hand, by using nanosilver paste as solder during welding, the low melting point of nanosilver can be utilized to achieve a firm connection between quartz glass and the material to be connected at a relatively low temperature, reduce the occurrence of thermal stress caused by high temperature that causes the quartz glass to crack, enhance the connection strength between the quartz glass and the material to be connected, and improve the connection reliability and stability between the quartz glass and the material to be connected; on the other hand, the excellent wettability of the nanosilver paste can ensure that it is evenly spread on the bonding surface of the quartz glass, and after subsequent melting, a firm welded joint can be formed, thus greatly improving the mechanical strength and reliability of the welded joint; on the other hand, after the welded joint is formed, by cooling the welded joint, the quartz glass and the material to be connected, the occurrence of thermal stress concentration that causes the quartz glass to crack can be further reduced, and then the mechanical strength of the welded joint and the connection strength between the quartz glass and the material to be connected can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of a process for welding quartz glass provided in an embodiment of the present application;
[0025] Figure 2 is the microstructure diagram of the welded joint;
[0026] Figure 3 for Figure 2 10 times magnified image. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the embodiments and technical features in the embodiments of the present application can be combined with each other, and the detailed description in the specific implementation method should be understood as an explanation of the purpose of the present application and should not be regarded as an improper limitation on the present application.
[0028] The present application is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The descriptions of "first", "second", etc. in the embodiments of the present application are only for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly including at least one feature. In the description of the embodiments of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically limited.
[0029] The present application embodiment provides a method for welding quartz glass, see Figure 1 , welding methods include:
[0030] S1, preparing nano silver slurry;
[0031] S2, coating the nano silver paste on the bonding surface of the quartz glass and the material to be connected;
[0032] S3, bringing the bonding surface of the quartz glass into contact with the bonding surface of the material to be connected, and melting the nanosilver paste to form a welding joint;
[0033] S4, cooling the weld joint, the quartz glass and the materials to be connected.
[0034] A welding method for quartz glass provided in an embodiment of the present application comprises first preparing a nanosilver paste, then coating the nanosilver paste on the bonding surface of the quartz glass and the material to be connected, then contacting and abutting the bonding surface of the quartz glass with the bonding surface of the material to be connected, then melting the nanosilver paste to form a welding joint, and finally cooling the welding joint, the quartz glass and the material to be connected. On the one hand, by using nanosilver paste as solder during welding, the low melting point of nanosilver can be utilized to achieve a firm connection between quartz glass and the material to be connected at a relatively low temperature, reduce the occurrence of thermal stress caused by high temperature that causes the quartz glass to crack, enhance the connection strength between the quartz glass and the material to be connected, and improve the connection reliability and stability between the quartz glass and the material to be connected; on the other hand, the excellent wettability of the nanosilver paste can ensure that it is evenly spread on the bonding surface of the quartz glass, and after subsequent melting, a firm welded joint can be formed, thus greatly improving the mechanical strength and reliability of the welded joint; on the other hand, after the welded joint is formed, by cooling the welded joint, the quartz glass and the material to be connected, the occurrence of thermal stress concentration that causes the quartz glass to crack can be further reduced, and then the mechanical strength of the welded joint and the connection strength between the quartz glass and the material to be connected can be further improved.
[0035] It should be noted that the cracking temperature of quartz glass is about 1200°C, while the melting point of nanosilver is far lower than the cracking temperature of quartz glass.
[0036] For example, in one embodiment, the material of the material to be connected can be a metal or a non-metallic material. In this way, the welding method provided by the present application can effectively solve the problems of poor wettability, low mechanical strength of the welded joint, and cracking of the quartz glass caused by thermal stress in the connection process between the quartz glass and the material to be connected.
[0037] In one embodiment, S1, preparing the nano silver paste, comprising:
[0038] S11, dispersing the nano silver particles in an organic solvent, adding a binder and a dispersant, and then stirring evenly to form the nano silver slurry.
[0039] Here, by dispersing the nano silver particles in an organic solvent first, the organic solvent can effectively disperse the nano silver particles in the solution to form a uniform dispersion system, which helps the nano silver particles to be evenly distributed on the bonding surface in the subsequent melting welding to improve the mechanical strength of the welded joint. Adding an adhesive and a dispersant, the adhesive can reduce the situation that the nano silver particles precipitate and gather at the bottom, and the dispersant can enhance the stability of the nano silver particles in the solvent, reduce the situation that the nano silver particles appear sedimentation and agglomeration. Finally, stirring it to ensure that all components are evenly mixed, so that a nano silver slurry with good fluidity and stability can be obtained.
[0040] In one embodiment, a magnetic stirrer can be used for stirring. For example, the magnet of the magnetic stirrer can be placed in the container and stirred at a speed of 500 rpm for 30 minutes. In this way, all components can be fully mixed evenly, and the fluidity and stability of the prepared nano-silver paste can be improved. The use of a magnetic stirrer for stirring facilitates the control of the stirring speed and stirring time, and the control is precise and the speed regulation is smooth.
[0041] In one embodiment, the organic solvent is ethanol and / or isopropanol. That is, the organic solvent may be ethanol, isopropanol, or a mixture of ethanol and isopropanol. Here, by selecting ethanol and / or isopropanol as the organic solvent, on the one hand, the nanosilver particles can be effectively dispersed in the solution to form a uniform dispersion system; on the other hand, the viscosity of the nanosilver slurry can be well adjusted, and then the fluidity of the nanosilver slurry can be controlled to meet the subsequent welding requirements; on the other hand, ethanol and isopropanol are inactive diluents, which can maintain the stable dispersion of the nanosilver particles in the solution and reduce the agglomeration and precipitation between the nanosilver particles.
[0042] In one embodiment, the particle size of the nanosilver particles is between 10nm and 100nm. Exemplarily, the nanosilver particles can be 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, etc. Here, by setting the nanosilver particles of appropriate particle size, on the one hand, after subsequent melting, a tight and uniform welding joint can be formed, and its thermal conductivity can be improved to effectively transfer heat; on the other hand, the melting temperature of the nanosilver slurry can be reduced to reduce the cracking of the quartz glass; on the other hand, after subsequent melting, the firmness of the nanosilver particles with the quartz glass and the materials to be connected is improved, and the adhesion is good, and the stability and reliability of the welding joint are improved; on the other hand, the nanosilver particles have a broad-spectrum antibacterial property, which can inhibit the growth and reproduction of a variety of pathogenic microorganisms to meet the needs of conductive and antibacterial scenarios.
[0043] In one embodiment, the adhesive may be polyvinyl alcohol. On the one hand, the hydroxyl groups of the polyvinyl alcohol molecular chain may interact with the functional groups on the surface of the nanosilver particles, thereby effectively dispersing the nanosilver particles and preventing them from agglomerating. Good dispersibility helps to form a uniform slurry, thereby improving the coating effect and sintering quality. On the other hand, the hydroxyl groups of the polyvinyl alcohol molecular chain may form hydrogen bonds or chemical bonds with the functional groups on the surface of the quartz glass and / or the material to be connected, thereby enhancing the bonding strength between the nanosilver slurry and the quartz glass and the material to be connected. The higher bonding strength may improve the stability and reliability of the welded joint. On the other hand, the addition of polyvinyl alcohol may adjust the fluidity and viscosity of the nanosilver slurry, thereby helping to obtain a uniform coating layer on the bonding surface and improving the subsequent welding effect. On the other hand, the hydroxyl groups of the polyvinyl alcohol molecular chain help to form a better conductive path for transmitting electrons, thereby improving the conductive properties of the nanosilver slurry.
[0044] In one embodiment, the adhesive may be polyethylene glycol. On the one hand, polyethylene glycol has good solubility and can be dissolved in a variety of solvents, thereby forming a uniform slurry with nanosilver particles, which helps to obtain a good coating effect and sintering quality; on the other hand, polyethylene glycol can reduce the surface tension between the nanosilver slurry and the quartz glass and the material to be connected, thereby enhancing its wettability, and good wettability helps the nanosilver particles to better adhere to the surface of the quartz glass and the material to be connected, thereby improving the sintering quality; on the other hand, the addition of polyethylene glycol can adjust the viscosity and fluidity of the nanosilver slurry, and appropriate viscosity and fluidity help to obtain a uniform coating layer and improve the sintering effect; on the other hand, the addition of polyethylene glycol can promote the sintering reaction between nanosilver particles, thereby increasing the sintering density and strength, thereby increasing the mechanical strength of the welded joint, and then increasing the stability and reliability of the welded joint.
[0045] In one embodiment, the weight percentage of the nanosilver particles in the nanosilver paste is 10% to 50%. Exemplarily, the weight percentage of the nanosilver particles in the nanosilver paste can be 10%, 20%, 30%, 40% or 50%, etc. Here, by setting the appropriate weight percentage of the nanosilver particles, on the one hand, the conductivity of the welding joint can be improved; on the other hand, through the larger specific surface area and higher surface activity of the nanosilver, it can form a stronger bond with the quartz glass and the material to be connected, and this strong bond helps to improve the shear strength and tensile strength of the welding joint, thereby improving the stability and reliability of the welding joint.
[0046] In one embodiment, S2, before coating the nano silver paste on the bonding surface of the quartz glass and the material to be connected, the welding method includes:
[0047] S5, sequentially performing organic solvent cleaning, ultrasonic cleaning and plasma cleaning on the quartz glass and the material to be connected.
[0048] For example, the quartz glass and the material to be connected may be placed in an ethanol solution to remove oil stains and particle impurities on the surface.
[0049] The quartz glass and the materials to be joined can then be placed in an ultrasonic cleaning device, for example, a frequency of 20kHz to 40kHz can be used for ultrasonic cleaning for 10min to 30min, so that fine contaminants on the surface can be further removed.
[0050] Finally, the quartz glass and the material to be connected can be placed in a plasma cleaning device. For example, low-pressure plasma can be used for surface treatment for 10 minutes to remove the residual oxide layer or other organic pollutants, enhance the activity of the surface of the quartz glass and the material to be connected, and improve the wettability of the nanosilver paste.
[0051] Here, the surfaces of the quartz glass and the materials to be connected can be cleaned by organic solvent cleaning, ultrasonic cleaning and plasma cleaning, which can not only improve the welding quality but also reduce welding defects and reduce the risk of thermal denaturation.
[0052] Exemplarily, in one embodiment, during the process of coating the nanosilver slurry on the bonding surface of the quartz glass and the material to be connected, a scraper or a coater can be used to evenly coat the prepared nanosilver slurry on the bonding surface of the quartz glass and the material to be connected, ensuring that the thickness of the nanosilver slurry is controlled within the set thickness, and then a microscope can be used to check the coating uniformity of the nanosilver slurry to reduce the occurrence of gaps or uneven thickness. Finally, the coated bonding surface is placed at room temperature to wait for the solvent in the nanosilver slurry to partially evaporate, which takes about 10 to 15 minutes, to ensure that the fluidity of the nanosilver slurry during the welding process is moderate.
[0053] In one embodiment, the thickness of the nanosilver paste on the bonding surface is between 40 μm and 50 μm. Exemplarily, the thickness of the nanosilver paste on the bonding surface can be 40 μm, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm, 46 μm, 47 μm, 48 μm, 49 μm or 50 μm, etc. In this way, by applying a suitable thickness of nanosilver paste, on the one hand, the contact area between the nanosilver particles and the quartz glass and the material to be connected can be increased, thereby improving the conductivity; on the other hand, the nanosilver particles can be more firmly bonded to the quartz glass and the material to be connected, thereby improving the mechanical strength and durability of the welded joint.
[0054] In one embodiment, a vacuum brazing device is used to melt the nano silver paste at a set temperature. Here, since there is a certain degree of vacuum in the vacuum brazing device, on the one hand, the influence of air on the welding process, such as oxidation and pollution, can be reduced, thereby improving the quality and reliability of the welded joint; on the other hand, the nano silver paste can be melted more evenly in the vacuum brazing to form a dense welded joint and improve the welding strength.
[0055] In one embodiment, the vacuum degree in the vacuum brazing equipment is 1×10 -3 Pa to 1×10 -5 For example, the vacuum degree in the vacuum brazing equipment can be 1×10 -3 Pa, 1×10 -4 Pa or 1×10 -5 Pa, etc. By setting the appropriate vacuum degree, the production of oxides during brazing can be reduced and the brazing quality can be improved.
[0056] In one embodiment, the set temperature is between 200° C. and 350° C. Exemplarily, the set temperature may be 200° C., 220° C., 250° C., 280° C., 300° C., 320° C., or 350° C., etc. Thus, by setting a suitable set temperature, the nanosilver paste may be melted at a lower temperature to reduce the thermal stress effect on the quartz glass and the material to be connected, reduce the occurrence of cracking of the quartz glass, and then improve the connection strength between the quartz glass and the material to be connected.
[0057] In one embodiment, during the process of melting the nano-silver paste, a set pressure is applied to the quartz glass and the material to be connected.
[0058] In this way, by applying a set pressure, on the one hand, the contact and diffusion between the nanosilver particles in the nanosilver paste and the quartz glass and the materials to be connected can be promoted, so as to more effectively fill the tiny gaps in the welding interface and form a denser sintered structure, which helps to improve the mechanical strength and conductivity of the welded joint; on the other hand, the pressure can ensure that the nanosilver paste is evenly distributed during the melting process, reducing the occurrence of local unmelted or uneven melting, and the uniform melting distribution helps to form a uniform welded joint and reduce welding defects such as pores and slag inclusions, thereby improving the welding quality; on the other hand, during the melting process, some organic matter in the nanosilver paste will decompose and produce gas. Applying a set pressure helps to discharge these gases, reduce the porosity in the welded joint, and thus improve the density and strength of the welded joint.
[0059] In one embodiment, the set pressure is between 1 MPa and 5 MPa. For example, the set pressure may be 1 MPa, 2 MPa, 3 MPa, 4 MPa or 5 MPa, etc. Thus, by setting a suitable set pressure, the mechanical strength and welding quality of the welded joint may be improved.
[0060] In one embodiment, the cooling rate of the weld joint, the quartz glass and the material to be joined is between 1° C. / min and 10° C. / min.
[0061] For example, the cooling rate of the weld joint, the quartz glass and the material to be connected may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc. Here, by setting a suitable cooling rate, the concentration of thermal stress caused by excessive cooling can be reduced, and the reduction of mechanical strength caused by cracks in the quartz glass can be reduced.
[0062] Exemplarily, in one embodiment, taking the connection between quartz glass and stainless steel as an example, a quartz glass sheet with a length of 20 mm, a width of 20 mm and a thickness of 2 mm is selected.
[0063] Preparation of nanosilver paste:
[0064] Firstly, take nano silver particles with a particle size of 50nm, prepare isopropyl alcohol organic solvent, polyvinyl alcohol adhesive and dispersant;
[0065] Dispersing the nanosilver particles in an isopropyl alcohol solvent at a weight percentage of 20% to ensure that the nanosilver particles are evenly distributed;
[0066] Adding 1% by weight of polyvinyl alcohol to the nanosilver solution, and then adding 0.5% by weight of a dispersant;
[0067] A magnetic stirrer was used to stir at 500 rpm for 30 min to ensure that all components were evenly mixed.
[0068] Surface cleaning:
[0069] Place quartz glass and stainless steel in an ethanol solution;
[0070] The quartz glass and stainless steel were placed in an ultrasonic cleaning device and ultrasonically cleaned at a frequency of 30 kHz for 20 min;
[0071] The cleaned quartz glass and stainless steel were placed in a plasma cleaning device and treated with low-pressure plasma for 10 min.
[0072] Nano silver paste coating:
[0073] Use a scraper or a coating machine to evenly coat the prepared nanosilver slurry on the bonding surface of the quartz glass and the stainless steel, and control its thickness to be 40 μm;
[0074] Use a microscope to check the uniformity of the nanosilver paste coating layer;
[0075] Place the coated bonding surface at room temperature and wait for the solvent in the nanosilver paste to evaporate, which takes about 10 to 15 minutes;
[0076] Melting Nano Silver Paste:
[0077] Place the quartz glass coated with nano-silver paste and stainless steel in a vacuum brazing device, ensure that the bonding surfaces are aligned, and apply appropriate pressure;
[0078] Start the vacuum brazing equipment and control the vacuum degree at 1×10 -4 Pa;
[0079] The set temperature was set to 300°C and the set pressure was applied to 2 MPa. After the heating temperature was raised to the set temperature, the set temperature and set pressure were maintained for 20 minutes.
[0080] Cooling process:
[0081] After brazing is completed, gradually reduce the temperature in the vacuum brazing equipment, and control the cooling rate at 5℃ / min;
[0082] After the temperature drops to room temperature, take out the brazed quartz glass and stainless steel and check the integrity and surface quality of the welded joint.
[0083] The quality of the prepared welding joints was tested: the welding joints had high mechanical strength, with a shear strength of 85 MPa, and excellent electrical and thermal conductivity. Figure 2 and Figure 3 is the microstructure diagram of the welded joint. Figure 3 for Figure 2 The 10 times magnified picture shows that the connection between the quartz glass and the material to be connected is relatively tight, and there is no cracking in the quartz glass.
[0084] The above is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. All modifications, equivalent substitutions, improvements, etc. within the spirit and principles of the present application are included in the protection scope of the present application.
Claims
1. A welding method for quartz glass, characterized in that: include: preparing nano silver slurry; Coating the nano silver paste on the bonding surface of the quartz glass and the material to be connected; Bringing the bonding surface of the quartz glass into contact with the bonding surface of the material to be connected, and melting the nanosilver paste to form a welding joint; The weld joint, the quartz glass and the materials to be joined are cooled.
2. The welding method according to claim 1, characterized in that: The preparation of the nano silver slurry comprises: The nano silver particles are dispersed in an organic solvent, and a binder and a dispersant are added, and then stirred evenly to form the nano silver slurry.
3. The welding method according to claim 2, characterized in that: The organic solvent is ethanol and / or isopropanol; and / or, The adhesive is polyvinyl alcohol or polyethylene glycol.
4. The welding method according to claim 2, characterized in that: The particle size of the nano silver particles is between 10 nm and 100 nm; and / or, The weight percentage of the nano-silver particles in the nano-silver paste is 10% to 50%.
5. The welding method according to claim 1, characterized in that: The thickness of the nano silver paste on the bonding surface is between 40 μm and 50 μm.
6. The welding method according to claim 1, characterized in that: Before coating the nano silver paste on the bonding surface of the quartz glass and the material to be connected, the welding method comprises: The quartz glass and the material to be connected are sequentially cleaned with an organic solvent, cleaned with an ultrasonic wave and cleaned with a plasma.
7. The welding method according to claim 1, characterized in that: During the melting of the nano-silver paste, a set pressure is applied between the quartz glass and the material to be connected.
8. The welding method according to claim 7, characterized in that: The set pressure is between 1 MPa and 5 MPa.
9. The welding method according to claim 1, characterized in that: The nano silver paste is melted by a vacuum brazing device at a set temperature, wherein the vacuum degree in the vacuum brazing device is 1×10 -3 Pa to 1×10 -5 Pa, and the set temperature is between 200°C and 350°C.
10. The welding method according to claim 1, characterized in that: The cooling rates of the weld joint, the quartz glass and the material to be connected are between 1° C. / min and 10° C. / min.
Citation Information
Patent Citations
A low-temperature sintered nano-silver paste and its preparation method
CN102290117A
Lead-free soldering-resistant electric conduction silver paste for electro-thermal film quartz glass tube electric heating piece and preparation method
CN103165220A
Vacuum brazing connection method for copper and skutterudite thermoelectric materials
CN118559134A
Inorganic LED packaging structure
CN213425012U
Solder connection of optical quartz glass with metals and method for the production thereof
DE1533542B1
Cited By
Laser welding method for enhancing glass-metal by spraying nano-particles through ultrasonic waves
CN121289757A